Development and initial validation of the MS score for diagnosis of macrophage activation syndrome in systemic juvenile idiopathic arthritis. Issue 10 (October 2019) - Minoia, Francesca; Bovis, Francesca; Davì, Sergio; Horne, AnnaCarin; Fischbach, Michel; Frosch, Michael; Huber, Adam; Jelusic, Marija; Sawhney, Sujata; McCurdy, Deborah K; Silva, Clóvis A; Rigante, Donato; et al.
Abstract : Objective: To develop and validate a diagnostic score that aids in identifying macrophage activation syndrome (MAS) in patients with systemic juvenile idiopathic arthritis (sJIA). Methods: The clinical and laboratory features of 362 patients with sJIA-associated MAS and 404 patients with active sJIA without evidence of MAS were collected in a multinational collaborative project. Eighty percent of the study population was used to develop the score and the remaining 20% constituted the validation sample. A Bayesian Model Averaging approach was used to assess the role of each clinical and laboratory variables in the diagnosis of MAS and to obtain the coefficients of selected variables. The final score, named MAS/sJIA (MS) score, resulted from the linear combination of these coefficients multiplied by the values of each variable. The cut-off that best discriminated MAS from active sJIA was calculated by means of receiver operating characteristic (ROC) curve analysis. Score performance was evaluated in both developmental and validation samples. Results: The MS score ranges from −8.4 to 41.8 and comprises seven variables: central nervous system dysfunction, haemorrhagic manifestations, active arthritis, platelet count, fibrinogen, lactate dehydrogenase and ferritin. A cut-off value ≥−2.1 revealed the best performance in discriminating MAS from active sJIA, with a sensitivity of 0.85, a specificity of 0.95 and a kappa value of 0.80. The good performance of the MS score was confirmed in the validation sample. Conclusion: The MS score is a powerful and feasible tool that may assist practitioners in making a timely diagnosis of MAS in patients with sJIA.